Students' perceptions of employability following a capstone course. Issue 4 (11th January 2019) - Gilbert, Guinevere; Wingrove, Dallas
Abstract : Purpose: Graduate employability represents a fundamental outcome of higher education. The purpose of this paper is to explore and compare students' perceptions of their employability through their experience of a simulated or real-life project. The context of the project is a capstone course, implemented in an Australian university, which was designed to enhance employability and foster transferable graduate attributes, including professional communication, interpersonal and leadership skills. Design/methodology/approach: The authors designed and conducted quantitative research to capture and measure students' perceptions of their employability at the conclusion of a capstone course over three consecutive years from 2015 to 2017. Findings: The results of this paper show that students undertaking a real-life project which makes a social contribution reported a significantly stronger development of work-ready skills in managing projects than students undertaking a simulation project. Specifically, interaction with industry and leadership were reported to be more developed. Originality/value: The study contributes to knowledge of the relationship between capstone learning and students' perceptions of employability. It advances the understanding of capstone course design and pedagogy which strengthens the link between learning and work.